Komodifikasi Ternak Tradisional di Sunda Kecil Tahun 1960-an Sampai 2017 - Pradita, Dennys; Wardhana, Adi Putra Surya (Universitas Negeri Yogyakarta, 2025)
Sunda Kecil is an area that has potential for farming. Most farms in this region are still traditional. Along with economic development policies, investment has begun to target farms in Sunda Kecil. When this article was written, research discussing the commodification of traditional farms in Sunda Kecil did not exist because most studies only focused on farm development techniques. Therefore, this research discusses (1) the reasons why Sunda Kecil has a tradition of farms; (2) the commodification of traditional farms in Sunda Kecil; (3) the influence of capitalism on the tradition of farms in Sunda Kecil. This research was compiled by collecting data, criticizing data, interpreting data, and compiling facts in a scientific narrative. Farms in Sunda Kecil fulfill the needs of food and life, such as horses, buffaloes, cows, and pigs. This potential has not been optimized, so the government conducted several policies to promote farms in Sunda Kecil, such as providing assistance for superior seeds, health employees, and artificial insemination. Modernization affected the pattern of farms in Sunda Kecil. Capital power has entered the economic joints that have the impact of changing the community's perspective on livestock. It is turned into a means to bring profit and change traditional farming towards modern farming.